An examination of the factors influencing Yemeni bank users’ behavioural intention to use internet banking services / Ali Hussein Saleh Zolait - Ali Hussein , Saleh Zolait (2007)
Investigating bank customers’ attitudes, perceptions, norms, behavioural controls and their influence on behaviour can be the right step in understanding the psychological factors affecting individuals to use Internet Banking (IB) in Yemen. This study attempted to provide such an understanding by elaborating Ajzen’s Theory of Planned Behaviour (TPB), a widely applied psychosocial theory in modelling behaviour. In addition, the Diffusion of Innovation (DOI) provides the widely applied concepts of the diffusion of innovation by modelling the attributes of innovation as part of attitudinal belief and the communication channels as part of normative belief. The purpose of this study was to examine the potential prominent factors relating to adopting and using Internet Banking in Yemen as a challenging context representative of developing countries. It also intended to scrutinize the role of Users’ Informational-based Readiness (UIBR) in the presence of other psychological determinants in predicting IB adoption as well as whether or not adopter groups differ from each other in terms of their readiness and the other theoretical factors, and whether or not UIBR is among the prominent predictors which contribute to IB adoption in Yemen. A sample of 369 bank customers was randomly obtained by means of a self administrated survey. A usable response rate of 59.2 % was achieved. SPSS version 14 was used to conduct a series of data analyses of variables assessment for validity and reliability tests and evaluation of regression models in both direct and indirect layers of predictors. The findings of the survey and the empirical bank website evaluation yield several findings. The results of multivariate tests showed that the direct predictors of attitude, Users’ Informational-based Readiness (UIBR), Perceived Behavioural Control (PBC) and Subjective Norm (SN) positively affect behavioural intention to use Internet banking. Cross- validating tests showed that all the direct predictors except SN could be generalized as the prominent predictors of IB. The overall prominent predictors, combined both direct and indirect, obtained in the study’s UR-TPB Model involved Relative Advantage/Compatibility (RAC), UIBR, Attitude, Observability, Technology Facilitating Condition, PBC and Self-efficacy. The model accounted for R2 = 75 percent of the variation of a person’s BI to use IB. The model’s accuracy was judged by the adjusted R2 =.75. The trimmed model explained substantial variance of Intention, Attitude and moderate variance of SN with substantial variance of PBC. In contrast to the rejecter groups, innovator and early adopter groups were represented by those of higher levels of awareness, experience, knowledge and exposure to IB. The respondents significantly viewed IB as advantageous, easy to use and not desirable to be observable. The study showed that IB use in Yemen is still not strong, and this could be due to the newness of IB in general. Banks in Yemen, based on the empirical evaluation of banks’ websites, indicated an acceptable level of informational presence while they were lagging behind at the transaction level. The study makes a significant contribution to theory and academic understanding of the adoption in areas of IS, and specifically IB in the Yemeni context which may guide policy makers and bankers towards the successful diffusion of innovations.